OR27-01 Combining Clinical and Genetic Approaches in Diagnosing a Large Brazilian Cohort of Patients with 46,XY Differences/Disorders of Sex Development (DSD) - Almeida Gomes, Nathalia Lisboa Rosa (J Endocr Soc, 2020)
Background: It is recommended a multidisciplinary approach consisted of clinical, hormonal and genetic workups for diagnosing 46,XY DSD. However, no previous study has quantified how useful is this combined approach. Objectives: To retrospectively review the clinical and genetic findings for diagnosing a large cohort of patients with 46,XY DSD from a single Brazilian center. Methods: 247 non-syndromic 46,XY DSD individuals (159 sporadic and 88 familial cases from 39 families) were studied. Clinical and hormonal data were collected from medical files. Testosterone (T), androstenedione (A) were measured by immunoradiometric or immunofluorimetric assays and dihydrotestosterone (DHT) by RIA after celite chromatography or by liquid chromatography tandem mass spectrometry; T/DHT and T/A ratios were calculated. Analysis of sensitivity (SE), specificity (SP) of T/DHT was performed, being the molecular diagnosis considered the gold standard for diagnosing SRD5A2 deficiency. A T/A>0.8 was considered indicative of 17ß-HSDB3 deficiency. The patients were clinically classified into four subgroups: 1) androgen insensitivity syndrome (AIS), 2) gonadal dysgenesis (GD); 3) defects in androgen synthesis (DAS) and 4) DSD of unknown etiology. Molecular studies were performed by Sanger sequencing and/ or massively parallel sequencing (MPS). Results: The median age at first visit was 14 years (range 0.1 to 59 years). The molecular diagnosis was established in 96.5% of the cases with AIS (n=28/29), in 96% of the subjects with DAS (n=46/48), in 36% of the patients with GD (n=21/57) and in 26.7% (n=15/56) with DSD of unknown etiology. The best cut-off for T/DHT in basal state and hCG stimulated was 12.5 (SE=100%; SP=78.57%) and 24 (SE=87.5%; SP=95.7%) respectively. A T/A<0.8 was observed in 13/16 (81%) of the patients with molecular diagnosis of 17ß-HSDB3 deficiency and also in 1/49 patients with other diagnose. Classification according to the phenotype matched with the genetic diagnosis in most cases. The molecular evaluation allowed that 16% (9/56) of the patients that were classified as DSD of unknow etiology had a definitive diagnosis, including six GD cases, two individuals with SRD5A2 deficiency and one with 17ß-HSDB3 deficiency. A clear AIS phenotype of five patients allowed us to consider and prove the pathogenicity of two synonymous and one promoter region variants as the cause of AIS. The combination of clinical and molecular diagnosis led to an increase in 8% the diagnosis in a total of 116 index-cases (58.5%) with a molecular diagnosis. Conclusion: Considering the phenotype heterogeneity, pitfalls of the hormonal assessment and number of genes involved, it is reasonable to consider MPS as a first test for diagnosing patients with 46,XY DSD. However, the combination of clinical and molecular diagnosis is more accurate than either strategies alone in diagnosing 46,XY DSD.